2001
DOI: 10.1079/bjn2000269
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and its relationship with postprandial metabolic changes after ingestion of different macronutrients in the morning

Abstract: The effect of carbohydrate, protein and fat ingestion on simple as well as complex cognitive functions and the relationship between the respective postprandial metabolic changes and changes in cognitive performance were studied in fifteen healthy male students. Subjects were tested in three sessions, separated by 1 week, for short-term changes in blood variables, indirect calorimetry, subjective performance and different objective performance tasks using a repeatedmeasures counterbalanced cross-over design. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 43 publications
2
55
5
Order By: Relevance
“…Fischer et al 18 argued that stable cognitive performance is related to a balanced glucose metabolism and metabolic activation state. They reported that carbohydrate ingestion resulted in relatively better short-term memory and accuracy of cognitive tasks concomitant with low metabolic activation, whereas protein ingestion resulted in better attention and efficiency of tasks concomitant with higher metabolic activation.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al 18 argued that stable cognitive performance is related to a balanced glucose metabolism and metabolic activation state. They reported that carbohydrate ingestion resulted in relatively better short-term memory and accuracy of cognitive tasks concomitant with low metabolic activation, whereas protein ingestion resulted in better attention and efficiency of tasks concomitant with higher metabolic activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found impaired performance with increasing arousal (Conners & Blouin, 1983), reduced arousal but no effect on performance (Lieberman et al 1983), better mood but no effect on performance for fed v. fasted subjects (Smith et al 1994c), or changes in performance but not mood (Smith et al 1988;Fischer et al 2001). This is perhaps not too surprising; causal relationships between mood and performance may well be neither contemporaneous (Owens et al 2000) nor linear: for instance, optimal attention or memory may require some, but not too much, arousal, alertness and anxiety (McGaugh, 1989;Smith, 1992;Reid & Hammersley, 1999).…”
Section: Associations Between Changes In Performance and Mood After Mmentioning
confidence: 99%
“…However, that is unlikely to account for the impaired cognitive performance, since it has been found that a carbohydrate-rich diet actually improves some task performance, albeit only in neurotic subjects (Markus et al 1999). Nevertheless, a diet particularly low in some fats might impair cognition (see p. 180; Fischer et al 2001).…”
Section: The Psychological Effects Of Dieting To Lose Weightmentioning
confidence: 99%
“…Cognitive impairment is associated with impaired glucose tolerance and hyperinsulinaemia in nondiabetic samples of elderly persons (29). Some studies suggest that stable performance is related to balanced glucose metabolism and state of metabolic activation (26). This may be mediated via an action of glucose on the cholinergic system (30).…”
Section: Glucose Tolerancementioning
confidence: 99%
“…Performance and the glycaemic index of foods Fischer et al (26) used test meals (400 kcal) of either pure CHO (glucose, maltodextrin and rice starch), protein or fat (a combination of saturated and unsaturated fatty acids). Protein ingestion resulted in better attention and efficiency on tasks, which was concomitant with higher metabolic activation.…”
Section: Effects Of Carbohydrates At Lunchtimementioning
confidence: 99%